Seasonal Clock Changes Are Underappreciated Health Risks—Also in IBD? - Föh, Bandik; Schröder, Torsten; Oster, Henrik; Derer, Stefanie; Sina, Christian (Frontiers in Medicine, 2019)
Today, daylight saving time is observed in nearly 80 countries around the world, including the European Union, the USA, Canada and Russia. The benefits of daylight saving time in energy management have been questioned since it was first introduced during World War I and the latest research has led to varying results. Meanwhile, adverse effects of seasonal time shifts on human biology have been postulated and the European Union is planning to abandon the biannual clock change completely. Medical studies have revealed a correlation of seasonal time shifts with increased incidences of several diseases including stroke, myocardial infarction and unipolar depressive episodes. Moreover, studies in mice have provided convincing evidence, that circadian rhythm disruption may be involved in the pathogenesis of inflammatory bowel diseases, mainly by disturbing the intestinal barrier integrity. Here, we present previously unpublished data from a large German cohort indicating a correlation of seasonal clock changes and medical leaves due to ulcerative colitis and Crohn’s disease. Furthermore, we discuss the health risks of clock changes and the current attempts on reforming daylight saving time from a medical perspective.